The Influence of E-Commerce, Parents Socio Economic Status, Self Control and Religiosity on Consumer Behavior - Putri, Nurul Adha; Sari, Nurma (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to determine the effect of e-commerce, parents' socioeconomic status, self-control and religiosity on Muslim consumer behaviour at the Faculty of Economics and Business at Syiah Kuala University. The research focuses on three things: simultaneous influence, partial influence and the most dominant variable. This study uses a correlational-based quantitative research method. The number of samples is 115 students. Data collection uses a questionnaire that is distributed online using Google Forms. The results showed those e-commerce variables, parents' socioeconomic status, self-control, and religiosity significantly affected Muslim student consumer behaviour. Partially, only e-commerce and religiosity variables have a significant effect, while two other variables, namely parents' socioeconomic status and self-control, do not significantly influence Muslim student consumer behaviour. At the same time, religiosity is the variable influence Muslim student consumer behaviour. The higher the level of religiosity, the more it will influence the consumption behaviour of Muslim students of the Faculty of Economics and Business at Syiah Kuala University.